Report on the project: Geophysical multilingual internet-driven information service (GeoMind) - SZALAIOVÁ, Viktória; SZALAIOVÁ, Eva (Contributions to Geophysics and Geodesy, 2008)
The aim of the GeoMind project is to develop a multilingual information system, which will provide the access to geophysical data holdings, it will integrate national databases and make them available via Internet on a certain level, offering cross-border, European-wide, unified electronic service. The project was launched in September 2006 and is planned for 24 months. The results of the preparatory phase, the analysis of the present practice and the present infrastructure of national geophysical information systems, including payment functions have determined the functional requirements of the planned system. Because of heterogeneity of existing data systems new metadata (and data) models should be elaborated. Data models are going to be used as standards in the project for data transfer between national databases and the web server of GEOMIND system. The participants are going to use these standards in possible future data exchange between them, or with third party institutions as well.